2014
DOI: 10.2478/ace-2014-0014
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Of The Casting Position Factor In Reinforced Concrete Elements In View Of Experimental Studies

Abstract: The paper presents the results of experimental investigations performed by the authors on the casting position factor. It was proved that at the height of reinforced concrete elements there are different bond conditions. Moreover, the bond depends on concrete mechanical properties, element height as well as concrete mix composition and consistency. The experiments also showed the advisability of determining the casting position factor separately for bars from normal concrete and those from high-performance con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…The way of applying the concrete mix is also important. [18] The results of classic destructive strength tests do not enable this phenomenon to be observed. Non-destructive ultrasonic testing allows this, but it is extremely rare to conduct such tests in construction practice.…”
Section: Introductionmentioning
confidence: 99%
“…The way of applying the concrete mix is also important. [18] The results of classic destructive strength tests do not enable this phenomenon to be observed. Non-destructive ultrasonic testing allows this, but it is extremely rare to conduct such tests in construction practice.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental research [4][5][6] prove that the phenomenon itself of HPC bond and the mechanism of its loss does not change compared with normal concretes. Neither do the factors affecting the bond although their individual contribution may vary what causes that the result of tests performed for normal concrete cannot be transferred directly to HPC.…”
Section: Previous Investigationsmentioning
confidence: 99%
“…The tensile strength, drying shrinkage, elastic modulus, and tensile relaxation of the overlay are affected to a great extent by curing conditions [57,[95][96][97]. It was also reported that the properties of concrete may be affected by the manner of casting [98][99][100]. The next method of improving overlay functional properties is surface hardening.…”
Section: Overview Of Recent Activities Used To Improve the Functionalmentioning
confidence: 99%